Peningkatan Hasil Belajar Matematika Siswa Kelas II Sekolah Dasar melalui Pendekatan Problem Based Learning di SDN 016 Bangkinang Kota - zulfah zulfah (Departement of Mathematics Education, 2024)
This Classroom Action Research (CAR) aims to describe how to Improve Mathematics Learning Outcomes of Grade II Elementary School Students through the Problem Based Learning Approach at SDN 016 Bangkinang City. This type of research is Classroom Action Research (CAR) which consists of 2 cycles. The subjects in this classroom action research (CAR) are Grade II students of SDN 016 Bangkinang City with a total of 20 students. The results of the study showed that in cycle I, the scores of the students' learning test results obtained an illustration that out of 20 students who were the subjects of the study, there were 16 or 80% who got scores in the poor category, and 4 students or 20% who got scores in the good category. This means that after the application of the problem-based learning (PBL) model, the learning outcomes of grade II students of SDN 016 Bangkinang City in cycle I increased but had not yet reached classical completeness. Therefore, the researcher continued the research in cycle II. The learning outcomes of students obtained in cycle II, namely 20 students who were the subjects of the study, showed that 100% of students achieved completeness with an average score of 84.75. This shows that the application of the problem-based learning model (PBL) with the improvements made after implementing cycle II has increased and has achieved classical completeness. In this case, the problem-based learning model can improve student learning outcomes in mathematics learning on the subject of flat shapes in class II of SDN 016 Bangkinang City.